Dermoscopic features predicting the presence of mitoses in thin melanoma. Issue 2 (May 2017) - Ribero, S.; Argenziano, G.; Lallas, A.; Moscarella, E.; Benati, E.; Raucci, M.; Piana, S.; Longo, C.
Highlights: The number of mitoses in the last AJCC classification upstage a melanoma has been included in the last AJCC classification as a factor for upstaging thin melanomas. Black colour and peripheral streaks can predict the presence of mitoses in thin melanoma. Atypical pigment network and brown colour are associated to thin melanoma without mitoses. Abstract: Background: The latest AJCC classification has included the number of mitoses as a factor for upstaging thin melanomas. Meanwhile, while dermoscopy has often been used to predict melanoma thickness, its value in predicting number of mitoses remains unknown. Objective: Our aim is to evaluate the correlation between dermoscopic features and the presence of mitoses in a consecutive cohort of thin melanomas. Methods: A case control study has been performed to identify specific dermoscopic parameters that could differentiate thin melanomas with 1 or more mitoses per mm2 from those without mitoses. Results: Of 177 melanomas equal to or thinner than 1 mm, 131 (74%) lesions had no mitoses and 46 (36%) lesions had at least 1 mitosis × mm2. Dermoscopic features associated with the presence of 1 or more mitoses were the following: peripheral streaks (OR 4.11; 95% CI 1.94–8.71) and black colour (OR 4.70; 95% CI; 2.28–9.68). In contrast, atypical pigment network (OR (0.30; 95% CI 0.15–0.61)) and brown colour (OR 0.36; 95% CI 0.18–0.75) were associated to melanomas without mitoses. The same variables were also associated to the increasing number of mitoses at linear regression. Conclusion: Black colour and peripheral streaks can predict the presence of mitoses in thin melanoma, while atypical pigment network and brown colour are associated to thin melanoma without mitoses.